2012
DOI: 10.1186/1471-2334-12-230
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of phenotypic and molecular methods for detection and differentiation of Candida albicans and Candida dubliniensis

Abstract: BackgroundCandida albicans is the most pathogenic Candida species but shares many phenotypic features with Candida dubliniensis and may, therefore, be misidentified in clinical microbiology laboratories. Candidemia cases due to C. dubliniensis are increasingly being reported in recent years. Accurate identification is warranted since mortality rates are highest for C. albicans infections, however, C. dubliniensis has the propensity to develop resistance against azoles more easily. We developed a duplex PCR ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 32 publications
0
41
0
3
Order By: Relevance
“…Additionally, when excluding the data for the two most frequent species, C. albicans and C. glabrata, in a sensitivity analysis, there were still significant differences between the three main PHYLO groups (A1Q6F, A1Q9A, A5Q7D) and for ITR (all had P values of Ͻ0.01) and FLC (all had P values of Ͻ0.002); the main message therefore remains. Although closely related isolates, e.g., C. albicans and C. dubliniensis, could be clearly separated (77,80) and showed a high probability of developing resistance to azoles (80)(81)(82), as reported in the literature, the MICs of C. dubliniensis may differ significantly (80). For example, despite the low numbers of C. dubliniensis isolates tested and the relatedness of C. dubliniensis to C. albicans, it could be demonstrated that C. dubliniensis, like other species, shows its own distinct group of susceptibility profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when excluding the data for the two most frequent species, C. albicans and C. glabrata, in a sensitivity analysis, there were still significant differences between the three main PHYLO groups (A1Q6F, A1Q9A, A5Q7D) and for ITR (all had P values of Ͻ0.01) and FLC (all had P values of Ͻ0.002); the main message therefore remains. Although closely related isolates, e.g., C. albicans and C. dubliniensis, could be clearly separated (77,80) and showed a high probability of developing resistance to azoles (80)(81)(82), as reported in the literature, the MICs of C. dubliniensis may differ significantly (80). For example, despite the low numbers of C. dubliniensis isolates tested and the relatedness of C. dubliniensis to C. albicans, it could be demonstrated that C. dubliniensis, like other species, shows its own distinct group of susceptibility profiles.…”
Section: Discussionmentioning
confidence: 99%
“…After extraction, DNA was quantified through Qubit™. The obtained DNA samples were subjected to PCR, according to the methodology described by Ahmad et al [8], using species-specific primers to amplify specific ITS1 and ITS2 regions of rDNA. For the identification of C. albicans, CALF (5'-3'TGGTAAGGCGGGATCGCTT) and CALR (5'GGTCAAAGTTTGAAGATATAC) primers were used.…”
Section: Molecular Identification By Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…albicans and C. dubliniensis are cryptic species and share several phenotypic characteristics, as germ tube formation and chlamydospore production, when grown on cornmeal agar [8]. Although some phenotypic characteristics slightly differ between these species, definite differentiation of C. albicans and C. dubliniensis relies on molecular methods [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, traditional methods of microorganism phenotyping have been replaced or added by the procedures associated to recombinant DNA [12][13][14] . Methods based on molecular markers are useful not only for phenotyping, but also for differentiation of Candida species [15][16] . The RAPD (Random Amplification Polymorphic DNA) allows the amplification of DNA sequences and is a simple and quick technique that does not require prior knowledge on the genomes to characterize organisms, using one randomly determined (usually a decamer) primer 17 .…”
Section: Introductionmentioning
confidence: 99%